2017
DOI: 10.3389/fphar.2017.00790
|View full text |Cite
|
Sign up to set email alerts
|

Reward Circuitry Plasticity in Pain Perception and Modulation

Abstract: Although pain is a widely known phenomenon and an important clinical symptom that occurs in numerous diseases, its mechanisms are still barely understood. Owing to the scarce information concerning its pathophysiology, particularly what is involved in the transition from an acute state to a chronic condition, pain treatment is frequently unsatisfactory, therefore contributing to the amplification of the chronic pain burden. In fact, pain is an extremely complex experience that demands the recruitment of an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 162 publications
1
46
0
1
Order By: Relevance
“…Indeed, we were the first to report that biological processes involved in neuroplasticity, within an HFD and sedentary behavior context, may prevent chronic pain susceptibility. In fact, several studies reported that genes implicated in the neuroplasticity in the NAc is related to chronic pain facilitation and hyperalgesia in humans and animals (Woolf, 2000;Apkarian et al, 2011;Mansour et al, 2014;Zhang et al, 2014;Kuner and Flor, 2016;DosSantos et al, 2017). However, it is important to emphasize that studies with humans from functional magnetic resonance imaging showed evidence that chronic pain and neuroplasticity are a cognitive maladaptive learning process (Apkarian et al, 2011;Mansour et al, 2014;DosSantos et al, 2017).…”
Section: Biological Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we were the first to report that biological processes involved in neuroplasticity, within an HFD and sedentary behavior context, may prevent chronic pain susceptibility. In fact, several studies reported that genes implicated in the neuroplasticity in the NAc is related to chronic pain facilitation and hyperalgesia in humans and animals (Woolf, 2000;Apkarian et al, 2011;Mansour et al, 2014;Zhang et al, 2014;Kuner and Flor, 2016;DosSantos et al, 2017). However, it is important to emphasize that studies with humans from functional magnetic resonance imaging showed evidence that chronic pain and neuroplasticity are a cognitive maladaptive learning process (Apkarian et al, 2011;Mansour et al, 2014;DosSantos et al, 2017).…”
Section: Biological Processesmentioning
confidence: 99%
“…In fact, several studies reported that genes implicated in the neuroplasticity in the NAc is related to chronic pain facilitation and hyperalgesia in humans and animals (Woolf, 2000;Apkarian et al, 2011;Mansour et al, 2014;Zhang et al, 2014;Kuner and Flor, 2016;DosSantos et al, 2017). However, it is important to emphasize that studies with humans from functional magnetic resonance imaging showed evidence that chronic pain and neuroplasticity are a cognitive maladaptive learning process (Apkarian et al, 2011;Mansour et al, 2014;DosSantos et al, 2017). Whereas studies with animal models investigated the role of one single molecular signaling related to neuroplasticity, such as BDNF/TrkB pathway, for instance (Zhang et al, 2014(Zhang et al, , 2017Wang et al, 2017).…”
Section: Biological Processesmentioning
confidence: 99%
“…In fact, we were the first to report that biological processes involved in neuroplasticity, at 11 least within an HFD-induce obesity and sedentary behavior context, may prevent the CP 12 susceptibility. Whereas several studies reported that neuroplasticity in the NAc is underlying CP in 13 humans and animals (Apkarian et al, 2011;DosSantos et al, 2017;Kuner and Flor, 2016;Woolf, 14 2000), our results may reflect an neurodegeneration process in the NAc caused by HFD and sedentary 15 behavior supporting the CP susceptibility, and secondarily, a neuroplasticity counter-regulatory 16 mechanism orchestrated by the voluntary PA. Indeed, PA and physical exercise is already known to 17 produce neuroplasticity Fernandes et al, 2017;Lourenco et al, 2019).…”
Section: Differential Gene Expression In the Nucleus Accumbens -Transmentioning
confidence: 59%
“…Chronic neuropathic pain is a devastating condition associated with maladaptive neural circuits in the brain. Abundant factors and neural circuits contribute to the experience of pain . The optical modulation of brain structures impacts both physical and emotional aspects of pain , which confirms the optogenetic approach in the control of pain perception .…”
Section: Introductionmentioning
confidence: 84%